2018
DOI: 10.1111/jdv.14929
|View full text |Cite
|
Sign up to set email alerts
|

The iris signal: blue periphery, tan collaret and freckles pattern – strong indicators for epidermal skin cancer in South‐Eastern Europe

Abstract: The results of this study sustain the hypothesis that blue periphery with light brown collaret and freckles iris pattern is a reliable phenotypic marker for epidermal skin cancer. The results of this study differ from previous reports in which skin cancer risk was associated with a homogeneous blue iris. We account these differences in the characteristics of the recruited patients (S-E European, skin type II and III). The assessment of iris colour patterns is an easy and inexpensive detection tool in skin canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Dear Editor, Risankizumab, a fully human IgG monoclonal antibody against interleukin (IL)-23, is a biologic agent recently approved for moderate-to-severe psoriasis treatment. 1 The recommended dose is 150 mg administered by two 75 mg subcutaneous injection at week 0, week 4 and every 12 weeks thereafter. 2 Clinical trials have shown its high efficacy and safety profile as well as its superiority compared to different class of biologics such as antitumour necrosis factor (TNF)-a (adalimumab), anti-IL12/23 (ustekinumab) and anti-IL-17 (secukinumab).…”
Section: Alopecia Universalis Improvement Following Risankizumab In A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Dear Editor, Risankizumab, a fully human IgG monoclonal antibody against interleukin (IL)-23, is a biologic agent recently approved for moderate-to-severe psoriasis treatment. 1 The recommended dose is 150 mg administered by two 75 mg subcutaneous injection at week 0, week 4 and every 12 weeks thereafter. 2 Clinical trials have shown its high efficacy and safety profile as well as its superiority compared to different class of biologics such as antitumour necrosis factor (TNF)-a (adalimumab), anti-IL12/23 (ustekinumab) and anti-IL-17 (secukinumab).…”
Section: Alopecia Universalis Improvement Following Risankizumab In A...mentioning
confidence: 99%
“…To the Editor: We read with great interest an article published in your journal in 2018 by M. Grigore et al with regard to iris patterns and risk of skin cancer in Southern Europe. 1 The eye and skin share the embryological ectoderm. Clinical risk factors for skin cancer include the blue or green-eyed phenotype.…”
mentioning
confidence: 99%
“…Both studies were completed in the non‐immunosuppressed general population. Grigore et al 2 first showed that skin cancer is associated with a blue periphery, blue colarete and presence of freckles in a South‐Eastern European population consisting of predominantly skin types two and three. Ridge et al 3 evaluated iris pattern and skin cancer risk in the Northern European population, predominant skin type one and two.…”
Section: Introductionmentioning
confidence: 99%
“…However, the eye colour is more complex because it is determined by our iris pattern which consists of an iris periphery, iris collarette and the presence/absence of iris freckles. 6 Iris pattern with a blue periphery, blue collarette and presence of freckles has recently been reported as a predictive risk factor for skin cancer in non-immunosuppressed South-Eastern European population consisting of predominantly skin types II and III 7 . Ridge et al 8 evaluated iris pattern and skin cancer risk in the Irish population which is mainly composed of skin types I and II.…”
mentioning
confidence: 98%
“…In particular, the OCA2, which is the gene responsible for albinism, codes for blue eyes. The iris collarette colour seems to have a less well‐known genetic origin, Leahy 6 and Grigore 7 found a light brown collarette to be a significant keratinocyte skin cancer risk factor in a predominant population of skin type II and III, while Ridge et al 8 . found a significant blue collarette colour significantly associated with most skin type I and II population.…”
mentioning
confidence: 99%